Avian haematozoan parasites and their associations with mosquitoes across Southwest Pacific Islands. - Ishtiaq, F; Guillaumot, L; Clegg, S; Phillimore, AB; Black, R; Owens, I; Mundy, N; Sheldon, B (2008)
The degree to which haematozoan parasites can exploit a range of vectors and hosts has both ecological and evolutionary implications for their transmission and biogeography. Here we explore the extent to which closely related mosquito species share the same or closely related haematozoan parasites, and examine the overlap in parasite lineages with those isolated from avian hosts, Zosterops species, sampled across the same study sites. Mosquito samples were collected and analysed (14 species, n = 804) from four islands in Vanuatu and the main island of New Caledonia. Using polymerase chain reaction, 15.5% (14/90) of pooled mosquito (thoracic) samples showed positive amplifications. Subsequent phylogenetic analysis of the cytochrome b gene identified four genetically distinct Plasmodium and two Haemoproteus lineages from these samples, five of which were identical to parasite lineages (n = 21) retrieved from the avian hosts. We found that three Plasmodium lineages differing by a maximum of 0.9% sequence divergence were recovered from different species and genera of mosquitoes and two Haemoproteus lineages differing by 4.6% sequence divergence were carried by 10 distantly related (11-21% divergent) mosquito species. These data suggest a lack of both cospeciation and invertebrate host conservatism. Without experimental demonstration of the transmission cycle, it is not possible to establish whether these mosquitoes are the biological vectors of isolated parasite lineages, reflecting a limitation of a purely polymerase chain reaction-based approach. Nonetheless, our results raise the possibility of a new transmission pathway and highlight extensive invertebrate host shifts in an insular mosquito-parasite system.